Antibacterial Activity of Bioactive Compound in Salvadora persica (Chewing Stick) Against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans - Haslinda Ramli; Rohazila Mohamad Hanafiah; Zalina Baharudin (ASM SCIENCE JOURNAL, 2024)
Indexed by SCOPUS/MYCITE